Sex differences in in vivo biomarkers of neurodegenerative dementia - Mak, Elijah; Kantarci, Kejal; Arvanitakis, Zoe (Frontiers in Dementia, 2025)
BackgroundAlzheimer’s disease (AD) and dementia with Lewy bodies (DLB) are two of the most common neurodegenerative diseases in older adults, and both show well-documented sex-specific differences in terms of clinical presentation, prevalence, and progression trajectories. However, the underlying neurobiological substrates that underpin these differences are poorly understood. In vivo biomarkers are well-suited to yield insights into how biological sex may shape disease pathophysiology in AD and DLB, and thus inform future research and precision medicine. The objective of this review is to synthesize recent evidence on sex differences related to biomarkers of AD and DLB.MethodsWe conducted a literature search of PubMed for studies published between January 2000 and May 2025 examining sex differences in neuroimaging and biofluid markers of mild cognitive impairment (MCI), AD, and/or DLB. Eligible studies were required to include sex-stratified or sex-interaction analyses in human participants with clinically defined MCI (due to AD or DLB), AD, or DLB.ResultsOf a total of 261 articles imported for screening, 63 met inclusion criteria, comprising 50 cross-sectional and 13 longitudinal investigations across biofluid markers (n = 18) studies, structural imaging (n = 18), functional imaging (n = 16), and molecular imaging (n = 11) studies. Women demonstrated initial cortical structural and metabolic advantages followed by accelerated decline. In MCI and AD, women were generally more susceptible to tau pathology and APOE ε4-related risk. In contrast, men with DLB showed greater metabolic and dopaminergic abnormalities, though women with DLB frequently exhibited mixed biomarker profiles. APOE ε4 conferred increased vulnerability in women for both conditions. Biofluid markers also revealed sex-specific expression patterns and associations with clinical outcomes.DiscussionThere is growing evidence that biological sex significantly influences the pathophysiology of AD and DLB as captured by in vivo biomarkers. These findings highlight the growing importance of analyses that consider sex differences in biomarker research and support the development of personalized diagnostic and therapeutic strategies in neurodegeneration. Future research should prioritize longitudinal studies to define optimal biomarker sequencing and therapeutic windows for each sex, while also investigating the genetic, hormonal, metabolic, pharmacological, and environmental mechanisms that underlie these sex differences, ultimately advancing precision medicine in neurodegenerative disease.